Taxonomic status of Paraguay’s only endemic bird, the Chaco Nothura Nothura chacoensis (Aves: Tinamidae) - Hayes, Floyd E.; Rodríguez, Oscar; Thalman, Erika R.; Castellanos, Emily A.; Sterling, John (Zootaxa, 2018)
The Chaco Nothura Nothura chacoensis Conover is endemic to the Chaco of western Paraguay. Originally described as a subspecies of the Spotted Nothura N. maculosa (Temminck), it has been regarded by many authorities as a distinct species based on alleged sympatry with N. maculosa. However, an earlier study revealed no differences in cytochrome b sequences between the two taxa. We reanalyzed the geographic distribution and morphological variation of N. chacoensis and N. maculosa in western Paraguay based on museum specimens. There is no locality where specimens of both taxa were collected, thus there is no evidence for sympatry. Morphologically the two taxa did not differ in any size or shape variable. Plumage characters overlapped in a few specimens. We recorded vocalizations from at least four individuals of N. chacoensis within its known range. Its typical territorial song was a very rapid, relatively monotone trill that was virtually identical with the most frequent territorial song of N. maculosa in length, number of notes, rate of notes, and emphasized frequency, and differed substantially from the songs of other species of Nothura. Based on distributional, morphological, biochemical, and especially vocalization data, we conclude that N. chacoensis should be regarded as a subspecies of N. maculosa.